School Head Leadership: Basis of Elementary Schools’ Performance in Castilla Districts, Division of Sorsogon - Jadie, Merlyn Joy (JPAIR Institutional Research, 2025)
This study aimed to assess the relationship between school head leadership and school performance of elementary schools in Castilla Districts, Sorsogon. Specifically, it described the level of school heads’ performance based on the OPCRF; described the performance of schools in terms of pupils’ academic performance in languages, mathematics, and science, teachers’ performance on IPCRF, and non-academic performance using key performance indicators (KPIs) such as enrolment rate, promotion rate, graduation rate, dropout rate, and cohort survival rate. Additionally, the study appraised the relationship between school heads’ performance, teachers’ performance, pupils’ performance, and KPIs, and proposed a school improvement plan for SY 2025–2026. The researcher selected public schools from Castilla East, West, and South, where school heads and teachers from these schools were chosen as participants regardless of their designation, using purposive sampling, and included only Grade 3 and Grade 6 pupils’ academic performance in English, Filipino, Mathematics and Science. These categories were assessed for SY 2022–2023 and SY 2023–2024 only. Data was analyzed using descriptive and correlational research design, employing document analysis and Pearson r integrating bootstrapping. Findings showed outstanding performance of school heads and teachers, high academic performance of pupils, and overall positive trajectory in KPIs. However, no significant relationship was found among the performance of school heads, pupils and KPIs, though a significant relationship was observed between school heads and teachers in SY 2023–2024. The proposed school improvement plan focused on Project S.E.A.L., Project Husay Kasanayan, and Brigada Pagbasa, Pagbilang, at Paglikha.